Current and Future Estimation of Glacier Retreat of nevado Cayambe, Ecuador - Cabrera Montenegro, Estefanía Belén; Vega Tamba, Joe Carlos; Jácome Aguirre, Gabriel Alexis (SATHIRI, 2023)
The Ecuadorian Andes experienced losses of glacier cover due to anthropic factors that promote climate change. This study aimed to quantify the loss of the glacier cover of Cayambe volcano located in Pichincha, Ecuador for the last decades (1990-2020) through Landsat satellite images. It includes the identification of how these changes relate to trends in climate variability and how they can continue over time through future projection. The result of the change in glacier coverage was obtained by digitizing satellite images and calculating the areas of the resulting polygons. Rainfall and temperature trends were performed using the Mann Kendall test and its relationship with glacier retreat. With the obtained areas the future projection of the glacier retreat and the tendency of decrease were applied. The glacier of Cayambe volcano had a decline of 30.09 % during the last 30 years due to the increase in temperature since 2012. The trends of the climatic variables are not significant, however, they present increasing trends for temperature and decreasing trends for precipitation, so they have a ratio of 4 to 7 % with glacier retreat, although it is not a high value, it is inferred that they are related. By 2050 the glacier will have an area of 6.1 km2 and by 2080 it will disappear. It can be concluded that this glacier is in constant decline with the variation of the years and the climate change becomes increasingly evident.
Keywords: Glacier retreat; climate variability; future projection